Escenas de lenguaje en la obra de Nicanor Parra - García, Pilar (Revista Chilena de Literatura, 2015)
In 1977 Cristian Huneeus noted that if Poems and Parra antipoems of Residencia en la tierra corresponds Neruda, would not entirely clear or obvious continuity or the problem of "artifacts" in its ambiguous ground between poetry and art object, between poetry and visual installation? Under this framework I propose a critical reading of Sermones y prédicas del Cristo de Elqui in dialogue with the order or change that critics have identified at this time of poetic production Parra. This is my shown in the issue of gender expressing the "sermons and preaching" and "Hojas de Parra", that Enrique Lihn later refers about the "tooks/speaks" that appears during the dictatorship and antipoetry assumes, recycle and incorporates them, in a beyond parody.